BRIDGING CULTURES: Teaching Indigenous People (IP) Learners from the Lenses of Teachers in a Public Elementary School - GUTIERREZ, RAFAEL; BABARAN, NILDA (International Journal of Arts, Sciences and Education, 2025)
Teachers play a significant role in realizing United Nation’s Sustainable Development Goal Number 4: Ensure Inclusive and Equitable Quality Education. This quest includes building an inclusive learning environment which serves as the very heart of indigenous people’s education. This qualitative study which utilized data triangulation through interviews, class observation, and journaling discusses the challenges and coping strategies of teachers in teaching indigenous people learners in the four recognized indigenous people schools of Aglipay West District of Schools Division Office of Quirino, Region II, Philippines. Findings indicate that contextualization of instructions, utilization of cultural resources, and leveraging dialects boost learning outcomes. However, to achieve these, teachers were required to demonstrate initiatives due to unavailability and limited access to culturally appropriate resources and other underlying challenges toward facilitating IP learners’ success. The key towards a culturally responsive and inclusive educational landscape lies in the shared actions of teachers, communities, and policymakers.